Technical and Environmental Assessment of the Consequences of Accidents on Offshore Gas Pipelines in the Baltic Sea - Masyutin, Yakov; Shcherban, Pavel; Gusev , Andrey; Vatagina , Anna (Transactions on Maritime Science, 2023)
The failure of the Nord Stream pipelines in the Baltic Sea in September 2022 had significant technical and economic consequences not only for the European Union energy sector and the gas production and transmission industry of the Russian Federation, but also entailed a number of environmental consequences, the scale of which has yet to be explored. During the preliminary assessment of the consequences of the accident, the team of scientists from the Kant Baltic Federal University, the Atlantic branch of the VNIRO and the Shirshov Oceanology Institute of the Russian Academy of Sciences calculated the composition of the gas mixture emitted and assessed its volume, studied potential environmental damage to the biogeocenoses of the Western and Southern Baltic, calculated the impact of the gases emitted on global temperature. The studies were based on data obtained from open sources and allow us to give a preliminary assessment of the environmental impact of the accident. The combination of analytical, evaluation and research methods used is basically a classic approach to accounting for the volume of gas emissions and their subsequent impact. Leakage volume was calculated by first determining the volume of gas that entered the natural environment after impact (before the emergency valves were closed), and then determining the second volume of gas (until pressure stabilization in the cut-off pipe sections and in the environment). Based on the information on the biota in the water area and the nature of the gas movement, an estimated impact on biological organisms in the zone of the Bronholm depression was determined. Based on the models of the influence of methane emissions on climatic parameters, the preliminary consequences of the emission were established. The assessment of the environmental impact on the water area was conducted and the main directions of further research determined. The potential ways to minimize the environmental consequences of the accident in the short and long term have been considered.